Psychiatric remuneration systems in Europe: an overview - McDaid, D. (Die Psychiatrie, 2011)
New forms of psychiatric remuneration linked to levels of activity undoubtedly will have an increasing role to play in mental health systems right across Europe. Potentially they can be more efficient and promote choice, but valid concerns have been raised about their impact on the sustainability and nature of psychiatric care. This article looks in particular at recent developments in England and the Netherlands and reflects on how remuneration mechanisms may need to develop further both to improve efficiency and quality within the context of an ever more fragmented and multi-sectoral mental health system. Any introduction of activity- based reimbursement should be introduced gradually. This should be accompanied by investment in adequate information systems to help better understand service utilisation patterns, transitional funding safeguards to reduce the risk of financial instability and incentives/ contractual measures to ensure that services strive to offer services of the highest possible quality that meet the needs of service users.
Keywords: Activity-based funding; remuneration; DRGs; psychiatry